Prototype Alat Pemberitahuan Kecelakaan Menggunakan Microcontroller Node MCU dan Sensor Crash - Natzir, Sadam Muhammad; Malahina, Edwin Ariesto Umbu (Jurnal Teknik Informatika dan Sistem Informasi, 2024)
This research has successfully developed a prototype for an automatic accident notification device using the Node MCU Microcontroller and Crash Sensor. The device is designed to detect accident incidents and provide a quick response by sending notifications containing the location of the accident through Short Messages (SMS/Telegram) to the relevant units in real-time. The Crash Sensor and Node MCU work together to detect and track incidents, while the GPS marking system and cellular communication module are used to track and send the coordinates of the accident location. The prototype was tested in various accident scenarios to test the accuracy and responsiveness of the system. The results showed that this prototype is capable of detecting and sending notifications about incidents with high speed and accuracy. The SIM800l module used in this prototype has a message delivery success rate of 90%. The implementation of this technology has the potential to increase the efficiency and effectiveness of emergency response to accidents, reducing handling time and potential further losses. Furthermore, this research indicates potential for further integration with traffic control systems or emergency services, which will form a more coordinated and effective response to accident incidents.